Comparison of Treatment of Emergent Adverse Events in Men with Premature Ejaculation Treated with Dapoxetine and Alternate Oral Treatments: Results From a Large Multinational Observational Trial. Issue 2 (1st February 2016) - Verze, Paolo; Cai, Tommaso; Magno, Carlo; Sabella, Francesco; Cucchiara, Vito; Palmieri, Alessandro; Mirone, Vincenzo
ABSTRACT: Introduction: Dapoxetine (DPX) has a pharmacokinetic profile suggesting a low rate of class-related adverse events (AEs). Aim: To assess the incidence of treatment emergent AEs (TEAEs) of special interest (known associations with selective serotonin reuptake inhibitors and/or potential clinically relevant AEs), and the related discontinuation rate in patients with premature ejaculation (PE) treated with DPX or alternate oral treatment (AOT), in routine clinical practice. Methods: In a prospective, 12-week, open-label, postmarketing observational, multinational study (PAUSE), 7545 patients were enrolled and divided into 2 groups: DPX 30–60 mg and AOT. Main outcome measures: The incidence rate of predefined TEAEs of special interest (mood and related, neurocognitive related, cardiovascular, urogenital and sexual function, accidental injury, and abnormal bleeding) in the DPX and the AOT groups, and the rate of AEs leading to study discontinuation. Results: The safety analysis was performed on 6128 patients treated with DPX and 1417 with AOT. The incidence of TEAEs of special interest in each AE category was greater for patients treated with AOT than with DPX. The higher differences were observed in the neurocognitive-related category (DPX 1.9% vs AOT 4.7%; P < .001), in the mood and related category (DPX 0.4% vs AOT 1.1%; P < .001), and in the urogenital system/sexual function (DPX 0.4% vs AOT 0.8%; P = .04). Cardiovascular TEAEs were the only AEs numerically greater in the DPX group (1.3 vs 1.6%, P = .34). The overall discontinuation rate was 10.9% in the DPX group and 6.9% in the AOT group). Conclusion: DPX has a favorable safety profile in terms of class-related TEAEs and clinically relevant AEs of special interest. In particular, it shows a significantly better safety profile in mood and related AEs, neurocognitive-related AEs, urogenital system, and sexual function, compared to the AOT group in the study population.